Implementation of Lean Office and Industry 4.0 Technologies to Enhance Administrative Efficiency, Productivity, and Organizational Sustainability: A Case Study in a Public Valuation Office - Jumali, Muhamad Abdul; Anjeli Riza Umami; Rusdiyantoro (2477 - 6165, 2025)
This study explores how the integration of Lean Office principles and Industry 4.0 technologies specifically IoT, AI, and Big Data for enhances administrative efficiency, productivity, and sustainability in professional service firms. A mixed-methods approach was adopted through surveys and interviews with 44 respondents from a public valuation office in Sidoarjo, Indonesia. Quantitative data were analyzed using multiple regression (R² = 0.908), revealing that Lean Office (β = 0.281, p = 0.016) and Industry 4.0 (β = 0.253, p = 0.020) significantly improved productivity. 93.18% of respondents acknowledged a reduction in process time after implementation, while 95.45% reported increased productivity. Furthermore, 98% agreed that interdepartmental collaboration improved after digital transformation. These findings suggest that lean-digital integration in administrative settings fosters adaptive work culture, reduces waste, and contributes to organizational sustainability.